Effect of Murotal Sound Stimulation during Pregnancy on the Number of Neuron Cells of Cerebrum and Cerebellum of the Newborn Rattus norvegicus - Ayu Putri Yani; Hermanto Tri Joewono; Widjiati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The human development index (HDI) illustrates how superior human resources are. Thestimulation of Murotal during growth and development has been shown to increase cell growth in plants.The aim of the study was to analyze the effect of the differences againts the number of neuron cell’s in thecerebrum and cerebellum Rattus norvegicus offspring between those who received Al-quran Murottal surahAr-Rahman stimulation, Qori and Qoriah sounds voice in pregnancy day of 6th. Methods: An Experimentalstudy using 30 pregnant (Rattus norvegicus). Subjects were randomized into three groups, control group(Q1), voice of Qori group (Q2), and voice of Qoriah group (Q3). sound stimulation was given on 6th-17thdays of pregnancy. From each mother, two Newborn of Rattus norvegicus were taken to make preparationsfrom brain tissue. Eosin Hematocycline was performed to assess number of neuron cells. Results : Thestudy shows that the mean and standard deviation of the number neuron cells cerebrum and cerebellum inthe control group is 9.88 ± 1.71 and 21.10 ± 2.11, the voice qori group is 10.16 ± 1.01 and 22.46 ± 1.71,and the voice qoriah group 11.12 ± 1.52 and 22.50 ± 1.76. ANOVAs statistical test results show there isno significant differences among groups with a value of p = 0.152 in the cerebrum and p=0.183 in thecerebellum. Conclusion : Murotal sound stimulation during pregnancy increased the number of neuron cellsin the cerebrum and cerebellum of newborn rats.